2011
DOI: 10.1016/j.matbio.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of valvular interstitial cell phenotype and function by hyaluronic acid in 2-D and 3-D culture environments

Abstract: Disruption of the extracellular matrix (ECM) is frequently found in calcific aortic valve disease (CAVD), yet the role of ECM components in valvular interstitial cell (VIC) function and dysfunction remains poorly understood. This study examines the contributions of exogenous and endogenous hyaluronic acid (HA), in both two-dimensional (2D) and 3D environments, in regulating the phenotype and calcification of VICs. VIC calcification was first assessed in a 2D setting in which the cells were exposed to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 48 publications
5
56
0
Order By: Relevance
“…However, whole aortic valve leaflets cultured in this study showed no apparent angiogenic or calcific changes in AVIC protein expression. Cell-ECM interactions within the leaflets may have affected the VIC response to hypoxia and have previously been shown to regulate calcification in the aortic valve [45,46]. ECM changes during valve disease are also associated with upregulation of the receptor for hyaluronan mediated motility, a receptor linked to angiogenesis [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, whole aortic valve leaflets cultured in this study showed no apparent angiogenic or calcific changes in AVIC protein expression. Cell-ECM interactions within the leaflets may have affected the VIC response to hypoxia and have previously been shown to regulate calcification in the aortic valve [45,46]. ECM changes during valve disease are also associated with upregulation of the receptor for hyaluronan mediated motility, a receptor linked to angiogenesis [47].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that VIC activation and calcification potential are measurably influenced by the substrate stiffness of the culture ECM or biomaterial [9]. Stiffer substrates such as polystyrene promote VIC calcification whereas collagen, hyaluronan, and fibronectin gels or surface coatings reduce calcification [11][12][13]. Production of calcific nodules by VICs is a complicated process, however, involving multiple cell signaling pathways that are influenced by inflammatory factors, growth factors such as TGF-ÎČ, substrate stiffness, biological activity of the substrate, and oxygen and nutrient availability [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Stiffer substrates such as polystyrene promote VIC calcification whereas collagen, hyaluronan, and fibronectin gels or surface coatings reduce calcification [11][12][13]. Production of calcific nodules by VICs is a complicated process, however, involving multiple cell signaling pathways that are influenced by inflammatory factors, growth factors such as TGF-ÎČ, substrate stiffness, biological activity of the substrate, and oxygen and nutrient availability [12][13][14][15][16][17]. 2D culture systems, such as bioactive surface coatings on tissue culture polystyrene, have been used to successfully isolate many of these factors for analysis but yield limited results when used to replicate the complex array of factors involved in CAVD.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronan is a large glycosaminoglycan that is abundant in the extracellular matrix of many tissues and is involved in vertebrate tissue morphogenesis and cellular processes (Noble, 2002;Spicer and Tien, 2004;Rosines et al, 2007;Garcia-Fuentes et al, 2009;Rodriguez et al, 2011). In the airways, it is an important component of the extracellular matrix in the lung parenchyma and plays a key role during lung development (Calvitti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%